2017
DOI: 10.1007/s00299-017-2177-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptional analysis of hop responses to infection with Verticillium nonalfalfae

Abstract: Key Message Dynamic transcriptome profiling revealed excessive, yet ineffective, immune response to V. nonalfalfae infection in susceptible hop, global gene downregulation in shoots of resistant hop and only a few infection-associated genes in roots. AbstractHop (Humulus lupulus L.) production is hampered by Verticillium wilt, a disease predominantly caused by the soil-borne fungus Verticillium nonalfalfae. Only a few hop cultivars exhibit resistance towards it and mechanisms of this resistance have not been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…Genome-wide transcriptome analysis of the V . nonalfalfae interaction with hop [ 45 ] revealed that 766 (81%) transcripts in the V . nonalfalfae in silico secretome were expressed in infected hop samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide transcriptome analysis of the V . nonalfalfae interaction with hop [ 45 ] revealed that 766 (81%) transcripts in the V . nonalfalfae in silico secretome were expressed in infected hop samples.…”
Section: Resultsmentioning
confidence: 99%
“…nonalfalfae genomes [ 22 ], transcriptomic and proteomic research of fungal growth on xylem stimulating medium [ 44 ] and RNA-seq studies of V . nonalfalfae –hop interactions [ 45 ]. A customized bioinformatics platform was used to set up a pipeline for prediction and characterization of the V .…”
Section: Introductionmentioning
confidence: 99%
“…Proteins were classified into four groups: Lectin-like proteins (A), Chitinases (B), Chitin deacetlyases (C) and Xyloglucan endotransglucosylase (D). Gene expression is presented as a heatmap of log 2 CPM values determined by RNA sequencing of infected hop (Progar et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-Seq library preparation from V. nonalfalfae infected hop at 6, 12, 18 and 30 days post inoculation (dpi) and data processing have been previously described (Progar et al 2017). Fungal transcripts were filtered out and their gene expression profiles were generated using the Hierarchical clustering with Euclidean distance method in R language (R Core Team 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, maximum GO terms were assigned for cellular component indicating need for large number of CDS for cellular component activity. Maximum GO terms were assigned for cellular component category in plants such as Humulus lupulus, Brassica rapa, Oryza sativa, Bupleurum chinense, Cassia obtusifolia and Chrysanthemum[51][52][53][54][55][56]. In the cellular component category, highest number of CDS were associated with "membrane" followed by "cell" in infected and control leaf samples which indicates the need of large number of transcripts for…”
mentioning
confidence: 99%